MARKETING MANAGEMENT AS A TOOL FOR ENSURING COMPETITIVE QUALITY OF PRODUCTS AND SERVICES (Economic journal of Lesya Ukrainka Volyn National University, 2025)
Introduction. In today's competitive environment, the quality of products and services is a key factor in a company's success. High quality builds consumer trust, increases brand value, and ensures market stability. At the same time, achieving competitive quality is impossible without effective marketing management, which not only identifies consumer needs but also shapes a comprehensive product development strategy. Marketing is increasingly seen as a tool for ensuring quality-from market analysis to managing customer expectations. This article examines the role of marketing management in improving the quality of products and services as a means of achieving competitive advantage.The purpose of the article. The purpose of this article is to study the role of marketing management in ensuring the competitive quality of products and services, as well as to identify practical tools and strategies that enable companies to increase their market efficiency by focusing on quality.Methods. The study uses analysis of scientific literature and publications, statistical analysis of marketing data, as well as systematic and comparative analysis to study the adaptation of marketing strategies in conditions of martial law. This comprehensive approach ensured a thorough investigation of the topic.Results. The study clearly showed that in conditions of martial law, marketing management plays a critical role in ensuring the competitive quality of products and services. The war has become a powerful challenge for Ukrainian businesses, which are forced not only to survive in conditions of instability, but also to seek new opportunities to maintain quality and consumer confidence.Market research has revealed significant changes in consumer behavior: in times of crisis, consumers become more demanding, focus on product quality and reliability, and pay attention to corporate social responsibility. This significantly increases the requirements for marketing strategies—companies must be transparent, honest, and active in communicating with their audience. It was found that most companies were forced to quickly revise their approaches to marketing, introducing digital tools, online communications, and remote forms of interaction with customers. This made it possible to maintain contact with consumers, respond quickly to their needs, and maintain a high level of service and product quality.At the same time, logistics problems and shortages of raw materials and resources have led to complications in production processes, threatening quality stability. For this reason, companies have been forced to strengthen their internal control systems and implement flexible quality management models that take into account both external and internal challenges. The integration of marketing processes with production and control functions has become particularly important, allowing for more rapid identification and elimination of quality issues. The results show that companies that have been able to effectively organize this interaction have significantly increased their competitiveness and have been able to maintain their reputation even in the most difficult conditions.Thus, the study confirms that marketing management focused on innovation, flexibility, digitalization, and social responsibility is now an indispensable mechanism for maintaining quality and competitiveness in Ukrainian business. This is not only a matter of survival, but also a strategy for the future that will help businesses adapt, develop, and become stronger after overcoming the crisis.Conclusiоns. Marketing management in a state of martial law is key to ensuring the competitive quality of products and services. Adapting marketing strategies, using digital technologies, and working closely with quality control help companies maintain customer trust and production stability. War changes consumer priorities, so marketing must be flexible and socially responsible. Businesses that have adapted quickly demonstrate greater resilience and readiness for recovery. Further research should focus on the development of digital tools and the integration of marketing with quality management to increase competitiveness in the post-crisis period.
Keywords: marketing management, competitive quality of products and services, digital technologies, quality management, consumer behavior, social responsibility.